IUTAM Symposium on Recent Advances in Moving Boundary Problems in Mechanics Proceedings of the IUTAM Symposium on Moving Boundary Problems, Christchurch, New Zealand, February 12-15, 2018 - Gutschmidt, Stefanie; Hewett, James N.; Sellier, Mathieu (IUTAM Bookseries,, 2019)
Many problems in mechanics involve deformable domains with moving boundaries, including fluid-structure interaction, multiphase flows, flows over soft tissues and textiles, or flows involving accretion/erosion to name but a few. The presence of a moving boundary presents considerable challenges when it comes to modelling and understanding the underlying system dynamics. This proceedings volume collects contributions made at the IUTAM Symposium on Recent Advances in Moving Boundary Problems in Mechanics held in Christchurch, New Zealand in February 2018.